College Readiness and First-Generation College Goers: Group Impacts with Students from an Urban, Predominantly African-American Population. Issue 3 (2nd September 2019) - Malott, Krista M.; Havlik, Stacey; Gosai, Shivam; Diaz Davila, Jose; Steen, Sam
Abstract : Researchers examined the experiences of two college preparatory groups with youth of color who are first-generation college-goers in an urban educational setting. An interpretive phenomenological framework was used to explore and identify participants' experiences of the intervention. The youth noted appreciation of the group format as a means for promoting enjoyment and personal self-disclosure. Self-disclosure promoted peer connection in regard to universal experiences which, in turn, deepened supportive relationships and college-going knowledge and skills.